Disturbed levels of non-enzymatic antioxidants and malondialdehyde among makeup users - Sameer Mohammed Yaseen; Hussein Adil Abid; Mudhar Abdul-Wahab Al-Obaidi (Journal of Techniques)
Makeup products contain heavy metals in variable amounts. Oxidative stress, damage, and aging could happen due to exposure to heavy metals. This study aimed to evaluate the concentrations of non-enzymatic antioxidants, and lipid peroxidation marker (malondialdehyde, MDA) in makeup and non-makeup users. 69 female students were sorted into two groups of 31 of non-makeup users (control group) and 38 of makeup users (case group). In this respect, the case group was also divided into 3 subgroups according to a period of 1.09±0.78 years (as mean±SD). 10 mL venous blood was drawn to determine the serum level of vitamin C, uric acid, glutathione (GSH) and MDA. The gained results were statistically analysed using SPSS. This in turn indicated a significant reduction in vitamin C, uric acid and GSH levels in makeup users compared to the control group. However, MDA concentrations were significantly higher in makeup users. A significant correlation between lipid peroxidation, dropping in non-enzymatic antioxidants and makeup products application was found.